In-Car Warnings of Emergency Vehicles Approaching: Effects on Car Drivers' Propensity to Give Way - Lidestam, Björn; Thorslund, Birgitta; Selander, Helena; Näsman, David; Dahlman, Joakim (Frontiers in Sustainable Cities, 2020)
Emergency driving entails substantially higher risk rates than ordinary driving, and it is crucial that other road users notice the emergency vehicles on call. Sirens and emergency lights are used to warn and demand that other road users give way and provide safe passage, but accidents still occur. The purpose of this study was to test the effect of a broadcast hyper local Emergency Vehicle Approaching (EVA) message via RDS radio, noticing that an emergency vehicle on call is approaching and demands that others give way, on the propensity of individual drivers to give way. In two simulator experiments, a total of 90 car drivers participated. In Experiment 1, drivers were passed three times by an ambulance in traffic conditions where it was easy to detect the ambulance early, and two versions of EVA message were compared to a baseline condition without a broadcast message. In Experiment 2, drivers were passed only once by an ambulance and in traffic conditions that made it difficult to detect the ambulance early, and either received an EVA message, or no message. The results showed that EVA messaging made drivers give way earlier and learned to give way earlier even without an EVA message. The main finding was that EVA messaging was necessary for making inexperienced drivers give way to an approaching emergency vehicle on call. Most of them did not know that they are obliged to give way, and some did not notice the emergency vehicle before it passed them. In conclusion, the study suggests that EVA messaging to alert and instruct drivers how to give way properly is beneficial for traffic safety and for enabling time-efficient emergency transports.